Collaboration to Accelerate Stunting Reduction in Laksamana Subdistrict - Nurmala Sari; Dwi Hartutik; Sulis Pratiwi; Hannisa Fitri Effendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Stunting is a major public health problem that has long-term impacts on the quality of human resources, affecting physical growth, cognitive development, and socio-economic outcomes. The Indonesian government has identified the acceleration of stunting reduction as a national priority, requiring cross-sector collaboration and active community participation. This article aims to describe the implementation and outcomes of a Community Service Program (Community Service) based on a collaborative approach to support stunting reduction efforts in Kelurahan Laksamana. The program employed a participatory method through health education, interactive discussions, and partnership strengthening among the community, health workers, and educational institutions. The results indicate an increased level of community awareness and understanding regarding stunting, the importance of routine health check-ups, and the role of families in stunting prevention. Furthermore, the program strengthened partnerships and enhanced community trust in local health services. This community service activity contributes positively to building collective awareness and serves as a strategic initial step toward sustainable stunting reduction at the local level.